Quality control of functioning of telecommunications systems - Волотка, В. С.; Скибин, В. П.; Андрушко, Д. В. (ХНУРЭ, 2010)
Quality control of functioning of telecommunication systems (TCS) is considered, based on the results of the statistical analysis of the spectral matrix of residual detunes ob-tained at the optimal state estimation of the different elements in the network. The recommendations are given on the method of forming the matrix of residual detunes.